Zyklon-B and Zyklon-C Warhead Detection Through Recycling of DU Wood : Theory and Practice - Pirot, Florent; Lavin, Claire; Mezhennaya, Maria (European Journal of Applied Sciences, 2025)
Depleted uranium-contaminated wood can be recycled as energy source and warhead tip through glyphosate plutogenization. This allows to present a simple answer to the use of DU warheads, that relies on the affinity of the glyphosate molecule for fast neutrons. Furthermore, such nuclear systems allow to detect zyklon-C warheads, and another system for detection of zyklon-B warheads, with sodium, is also presented. While crematory contamination in wood reduces the yield of glyphosate plutogenization, sodium allows to overcome that issue.